Diagonalizing the trace form in some number fields - Dąbrowska, Anna (Annales Mathematicae Silesianae, 2001)
In the present paper the trace form on the ring of integers of a number field is considered. All quadratic fields are determinated for which the form can be diagonalized, i.e. the quadratic fields with an integral basis orthogonal with respect to the trace. There are also given examples of fields of higher degree with the same property.